2010
DOI: 10.4161/cbt.9.12.11880
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of ATP6V1C1 expression in brush cytology samples as a diagnostic and prognostic marker in oral squamous cell carcinoma

Abstract: It was confirmed that ATP6V1C1 levels were significantly higher in patients with OSCC than in healthy controls, with expression increasing with higher tumor stage. ROC analysis showed that the measurement of ATP6V1C1 expression levels is a highly sensitive and specific diagnostic method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 58 publications
0
34
0
2
Order By: Relevance
“…Furthermore, overexpression of particular V-ATPase subunits has been observed in both human cancer cell lines and human tumor samples. For example, subunit V 1 C is overexpressed in oral squamous cell carcinoma samples (47,141,147), and subunit V 0 c is overexpressed in human hepatocellular carcinoma samples (216) and pancreatic cancer samples (139). Expression of subunit V 1 E and subunit V 1 A is increased in pancreatic cancer and gastric cancer, respectively, and expression correlates with tumor grade (23,101).…”
Section: A Expression and Localization Of V-atpases In Tumor Cellsmentioning
confidence: 99%
“…Furthermore, overexpression of particular V-ATPase subunits has been observed in both human cancer cell lines and human tumor samples. For example, subunit V 1 C is overexpressed in oral squamous cell carcinoma samples (47,141,147), and subunit V 0 c is overexpressed in human hepatocellular carcinoma samples (216) and pancreatic cancer samples (139). Expression of subunit V 1 E and subunit V 1 A is increased in pancreatic cancer and gastric cancer, respectively, and expression correlates with tumor grade (23,101).…”
Section: A Expression and Localization Of V-atpases In Tumor Cellsmentioning
confidence: 99%
“…Other studies have described expression of V‐ATPase/specific subunits in pancreatic cancer,32, 33 nonsmall cell lung cancer,34 oral squamous cell carcinoma,35, 36 ovarian cancer,37 cervical cancer,38 breast cancer,39, 40 gliomas,41 and hepatocellular carcinoma 42. A summary of studies investigating clinical significance of V‐ATPase in cancer is provided in Table 1.…”
Section: Dysregulation Of V‐atpase In Cancermentioning
confidence: 99%
“…We believe that the future of these molecules in cancer treatment involves measuring the overexpression of specific V-ATPase subunits in tumors to be treated and then using inhibitors specific for the subunits being expressed , Perez-Sayans et al 2010). This will allow clinicians to provide more specific treatment, while also minimizing adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that V-ATPases, which secrete protons through the plasma membrane, may play a key role in the acidification of the tumor environment ). Several human tumor cells are characterized by increased V-ATPase expression and activity (Perez-Sayans et al 2010), and pretreatment with proton pump inhibitors (PPIs) has been found to sensitize tumor cell lines to the effect of different chemotherapy drugs (De Milito, Fais 2005a, Luciani et al 2004, De Milito, Fais 2005b, Sennoune, Luo & MartinezZaguilan 2004. The effectiveness of the drug transport mechanism appears to be comparable to that of drug efflux pumps such as Pgp, although vesicle acid exchange (above all in vesicles that have an active H+/cation exchange system) may be an important factor in drug resistance, and particularly in cells that do not overexpress Pgp-type efflux pumps in the plasma membrane ).…”
Section: The Role Of V-atpases In Multidrug Resistancementioning
confidence: 99%